Metal–Organic Frameworks: Trapping and Releasing of Oxygen in Liquid by Metal–Organic Framework with Light and Heat (Small 22/2021). Issue 22 (2nd June 2021) - Fujimura, Masashi; Kusaka, Shinpei; Masuda, Ayaka; Hori, Akihiro; Hijikata, Yuh; Pirillo, Jenny; Ma, Yunsheng; Matsuda, Ryotaro
Abstract : In article number 2004351, Ryotaro Matsuda and co‐workers present a bifunctional MOF that exhibits activation of triplet oxygen into singlet oxygen under UV‐light irradiation and the successive oxygen trapping in liquids, providing a paradigm shift in the field of gas adsorption in MOF nanospace from "gas‐phase molecular adsorption" to "liquid‐phase molecular adsorption."